1997
DOI: 10.1051/rnd:19970605
|View full text |Cite
|
Sign up to set email alerts
|

Classification and quantification of abnormal sperm along the epididymal tract. Comparison between adult and aged hamsters

Abstract: Summary ― The types and averages of abnormal sperm were studied in the epididymis of adult and aged golden hamsters. Abnormal spermatozoa represent 14.6-19.6% of the total of spermatozoa in adults, 31.7-42. 1 % in middled-aged hamsters, and 39.3-50% in advanced-aged hamsters. Twelve abnormal shapes were found, with the lack of an acrosome, the lack of a head, and the coiling of the tail, being the most frequent in the three age groups. An important increase in the number of coiled spermatozoa was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…All the alterations we observed in the epididymis of aged animals probably also affect sperm maturation. We previously found that the epididymis is responsible for the increase in the percentage of abnormal sperm in aged hamsters (Calvo et al, 1997b). However, both the epididymis and testis (which is seriously altered in the aged hamster) are probably responsible for the impairing of reproductive ability that hamsters suffer during aging.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All the alterations we observed in the epididymis of aged animals probably also affect sperm maturation. We previously found that the epididymis is responsible for the increase in the percentage of abnormal sperm in aged hamsters (Calvo et al, 1997b). However, both the epididymis and testis (which is seriously altered in the aged hamster) are probably responsible for the impairing of reproductive ability that hamsters suffer during aging.…”
Section: Discussionmentioning
confidence: 97%
“…Little is known about the alterations of sperm present in the epididymis of aged animals. We have previously observed that aged hamsters present a higher percentage of abnormal sperm (evaluated by light and electron microscopy) but present few new types of abnormal shapes (Calvo et al, 1995, 1997b).…”
mentioning
confidence: 96%
“…Generally speaking, spermatozoa grow to maturity, passing through the epididymis, i.e., development of motility, changes in acrosome, induction of chromatin condensation and migration of cytoplasmic droplets 33) . Testicular histopathological changes do not correlate with sperm tail abnormalities in bulls 33) , and most tail abnormalities are induced during epididymal transit of spermatozoa in the boar and hamster 35,36) . Finally, we need to address the relevance of the results in the present study to risk assessments of actual human exposure to OPs.…”
Section: Discussionmentioning
confidence: 99%
“…The risks inherent in tranquilization or anesthesia limit the frequency with which collections can be performed. However, occasional or sporadic semen collection does not yield information reflective of sperm production potential because sperm quality declines over time in the epididymis [Cuasnicu and Bedford, 1989;Calvo et al, 1997;Noirault and Brillard, 1999]. Therefore, a noninvasive method of semen collection must be employed to compile a meaningful series of ejaculates that will describe a male's reproductive capacity.…”
Section: Introductionmentioning
confidence: 99%